PENGARUH CURRENT RATIO DAN TOTAL ASSET TURNOVER TERHADAP RETURN ON ASSET PADA PT PAN BROTHERS TBK PERIODE 2012-2022 - Dwi lestari; Achmad Ludvy (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to determine the effect of Current Ratio (CR) and Total Asset Turnover (TATO) on Return On Assets (ROA) at PT Pan Brothers Tbk for the period 2012-2022. This type of research is quantitative descriptive with the analysis method used with descriptive statistics, classical assumption tests, hypothesis tests (t-test and F-test) and determination coefficient tests (R^2) with a significance level of 0.05 (5%) and the sources used are secondary data. The results of this study indicate that the Current Ratio (CR) on Return On Assets (ROA) has a negative and significant effect, this is evidenced by the results of data processing from the t_count value -2.351 < t_table 2.306 and a significant value of 0.047 < 0.05. Total Asset Turnover (TATO) has a significant effect on Return On Asset (ROA), this is evidenced by the results of data processing from the t_count value of 2.483> 2.306 and a significant value of 0.038> 0.05. Simultaneous testing shows that Current Ratio (CR) and Total Asset Turnover (TATO) simultaneously have a significant effect on Return On Asset (ROA), this is evidenced by the results of data processing of these values, this is evidenced by the results of data processing F_count 8.182> F_table 3.11 with a significant value of 0.012 <0.05. Then the variables Current Ratio (CR) and Total Asset Turnover (TATO) contribute 67.2% to Return On Asset (ROA). Meanwhile, the remaining 42.3% is influenced by other factors not explained in this study.